Materialism in Pentecostal churches. Case study of selected churches in Nakuru County - Doreen Nyamosi, (IJRDO - Journal of Social Science and Humanities Research, 2019)
African Pentecostal Christianity has seen many phases of expressing spirituality since the European colonial authorities left Africa. Many of the African churches that started during and after colonialism were mainly driven by protest against white domination and fight for independence. It is almost fifty years after the independence of most African nations and Christianity in Africa is now importing foreign traits of Christianity namely, Pentecostalism, whose modern origin is the Azusa Street Revival of 1873 – 1929, in Topeka, Kansas. Pentecostal Christianity and its materialistic approach to spirituality, which defies biblical teaching on the same, have been overwhelmingly embraced in Africa. Pentecostal Christianity, largely an import of American Christianity, has now become a popular expression of spirituality in Kenya. This study focused on the materialism: desire to be wealthy and healthy, as distinctive characteristics of Pentecostalism in Nakuru town. Prosperity gospel was evaluated in light of the teaching of the Scriptures. Churches in Nakuru were selected through the use of in-depth interviews to know what views the prosperity gospel teaching pastors held on success, health and material wealth. Questionnaires were issued to the youth, men and women in Pentecostal churches that have embraced prosperity gospel teachings, to determine their views on the same. The data was analysed with the intention of comparing and contrasting the findings in the field concerning prosperity with the biblical position on the same and found out that there is deception in the presentation of prosperity gospel. Pastors who present prosperity gospel twist the Scriptures so as to make money out of the unsuspecting congregants. Theological knowledge was found wanting among pastors and their congregations. Therefore, it is highly recommended that pastors get exposed to adequate theological training before they lead churches.